(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
An analysis is presented for the effects of heat generation and chemical reaction with porosity variation of spilled oil in the subsurface. The dimensionless governing equations are solved using the perturbation method. The equations of momentum includes thermal and concentration buoyancy effects, energy equation include heat generation and the equation of species includes in chemical reaction. Solution of velocity, temperature and concentration profiles are presented graphically with several values of parameter.